Designing Multivalent Ligands to Control Biological Interactions: From Vaccines and Cellular Effectors to Targeted Drug Delivery. Issue 2 (4th January 2019) - Arsiwala, Ammar; Castro, Ana; Frey, Steven; Stathos, Mark; Kane, Ravi S.
Abstract: Multivalent interactions in which multiple ligands on one object bind to multiple receptors on another are commonly found in natural biological systems. In addition, these interactions can lead to increased strength and selectivity when compared to the corresponding monovalent interaction. These attributes have also guided the design of synthetic multivalent ligands to control biological interactions. This review will highlight the recent literature describing the use of multivalent ligand display in the design of vaccines, immunomodulators, cell signaling effectors, and vehicles for targeted drug delivery. Abstract : By design : While multivalent interactions, in which multiple ligands on one object bind to multiple receptors on another, are commonly found in nature, there is also significant interest in designing multivalent ligands to control biological interactions. This review primarily focuses on recent applications of multivalency in the design of vaccines, immunomodulators, cell signaling effectors, and vehicles for targeted drug delivery.